High-efficiency grating-couplers: demonstration of a new design strategy. Issue 1 (December 2017) - Marchetti, Riccardo; Lacava, Cosimo; Khokhar, Ali; Chen, Xia; Cristiani, Ilaria; Richardson, David; Reed, Graham; Petropoulos, Periklis; Minzioni, Paolo
Abstract We present a simple and practical strategy that allows to design high-efficiency grating couplers. The technique is based on the simultaneous apodization of two structural parameters: the grating period and the fill-factor, along with the optimization of the grating coupler etching depth. Considering a 260 nm Si-thick Silicon-on-insulator platform, we numerically demonstrated a coupling efficiency of −0.8 dB (83%), well matching the experimental value of −0.9 dB (81%). Thanks to the optimized design, these results represent the best performance ever reported in the literature for SOI structures without the use of any back-reflector.